2018
DOI: 10.1136/jramc-2017-000872
|View full text |Cite
|
Sign up to set email alerts
|

Does the addition of hyperbaric oxygen therapy to conventional treatment modalities influence the outcome of soldiers with idiopathic sudden sensorineural hearing loss?

Abstract: HBOT plus existing conventional treatment was associated with a better outcome than conventional treatment alone. We would recommend the addition of HBOT is recommended as a first-line treatment modality for all soldiers presenting with ISSNHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Ten suitable trials involving 1295 patients were retrieved (Table 3 ) [ 17 25 ]. A study conducted by Topuz et al, demonstrated an average of the hearing gain at five contiguous frequencies significantly higher in the HBO + SS group for patients with severe or profound hearing impairment (respectively, p = 0.014 and p = 0.005) [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten suitable trials involving 1295 patients were retrieved (Table 3 ) [ 17 25 ]. A study conducted by Topuz et al, demonstrated an average of the hearing gain at five contiguous frequencies significantly higher in the HBO + SS group for patients with severe or profound hearing impairment (respectively, p = 0.014 and p = 0.005) [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, this difference was not significant ( p = 0.754) [ 22 ]. In three studies, a significant improvement was found after the addition of HBO therapy [ 23 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous research into HBOT for SSNHL included 12 randomized controlled trials (RCTs), 5 , 6 , 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 and three meta‐analyses. 8 , 9 , 10 A significant trial by Krajcovicova et al 5 reported an 11.5 dB improvement in hearing when HBOT supplemented pharmacotherapy as a first‐line treatment for SSNHL.…”
Section: Discussionmentioning
confidence: 99%
“…In both groups, therapy was initiated early, on average within 4 days. Complete hearing recovery was significantly better in the HBOT group after 180 days (27% vs 10%, P = 0.043) [ 121 ].…”
Section: Clinical Use Of Hyperbaric Oxygen Therapymentioning
confidence: 99%
“…Examples of treatments are blood flow-promoting agents, vasodilators, diuretics, dextran and pentoxifylline. However, many of those studies (Chi, Liu, Ohno, Satar, Narozny, Aslan, Topuz, Racic) have failed to show effectiveness in the clinical setting [ 81 84 , 91 , 104 , 105 , 121 ].…”
Section: Clinical Use Of Hyperbaric Oxygen Therapymentioning
confidence: 99%